Cardiovascular outcomes with sodium–glucose cotransporter-2 inhibitors vs other glucose-lowering drugs in 13 countries across three continents: analysis of CVD-REAL data - Khunti, Kamlesh (Cardiovasc Diabetol, 2021)
BACKGROUND: Randomized, controlled cardiovascular outcome trials may not be fully representative of the management of patients with type 2 diabetes across different geographic regions. We conducted analyses of data from the multinational CVD-REAL consortium to determine the association between initiation of sodium–glucose cotransporter-2 inhibitors (SGLT-2i) and cardiovascular outcomes, including subgroup analyses based on patient characteristics. METHODS: De-identified health records from 13 countries across three continents were used to identify patients newly-initiated on SGLT-2i or other glucose-lowering drugs (oGLDs). Propensity scores for SGLT-2i initiation were developed in each country, with 1:1 matching for oGLD initiation. In the matched groups hazard ratios (HRs) for hospitalization for heart failure (HHF), all-cause death (ACD), the composite of HHF or ACD, myocardial infarction (MI) and stroke were estimated by country, and pooled using a weighted meta-analysis. Multiple subgroup analyses were conducted across patient demographic and clinical characteristics to examine any heterogeneity in treatment effects. RESULTS: Following matching, 440,599 new users of SGLT-2i and oGLDs were included in each group. Mean follow-up time was 396 days for SGLT-2i initiation and 406 days for oGLDs initiation. SGLT-2i initiation was associated with a lower risk of HHF (HR: 0.66, 95%CI 0.58–0.75; p < 0.001), ACD (HR: 0.52, 95%CI 0.45–0.60; p < 0.001), the composite of HHF or ACD (HR: 0.60, 95%CI 0.53–0.68; p < 0.001), MI (HR: 0.85, 95%CI 0.78–0.92; p < 0.001), and stroke (HR: 0.78, 95%CI 0.72–0.85; p < 0.001); regardless of patient characteristics, including established cardiovascular disease, or geographic region. CONCLUSIONS: This CVD-REAL study extends the findings from the SGLT-2i clinical trials to the broader setting of an ethnically and geographically diverse population, and across multiple subgroups. Trial registration NCT02993614 SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12933-021-01345-z.